Chronic Pancreatitis and the Development of Pancreatic Cancer - Kandikattu, Hemanth K.; Venkateshaiah, Sathisha U.; Mishra, Anil (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Pancreatitis is a fibro-inflammatory disorder of the pancreas that can occur acutely or chronically as a result of the activation of digestive enzymes that damage pancreatic cells, which promotes inflammation. Chronic pancreatitis with persistent fibro-inflammation of the pancreas progresses to pancreatic cancer, which is the fourth leading cause of cancer deaths across the globe. Pancreatic cancer involves cross-talk of inflammatory, proliferative, migratory, and fibrotic mechanisms. In this review, we discuss the role of cytokines in the inflammatory cell storm in pancreatitis and pancreatic cancer and their role in the activation of SDF1α/CXCR4, SOCS3, inflammasome, and NF-ΚB signaling. The aberrant immune reactions contribute to pathological damage of acinar and ductal cells, and the activation of pancreatic stellate cells to a myofibroblast-like phenotype. We summarize several aspects involved in the promotion of pancreatic cancer by inflammation and include a number of regulatory molecules that inhibit that process.
Keywords: cytokines